2016
DOI: 10.1111/bdi.12446
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing medication‐free subjects with unipolar disorder from subjects with bipolar disorder: state matters

Abstract: For the first time, we showed that medication-free subjects with MDD and BD can be differentiated based on structural MRI as well as resting-state functional connectivity. Importantly, the results indicated that research concerning diagnostic neuroimaging tools distinguishing between MDD and BD should consider mood state as only depressed subjects with MDD and BD could be correctly classified. Future studies, in larger samples are needed to investigate whether the results can be generalized to medication-naïve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 106 publications
(196 reference statements)
3
40
0
Order By: Relevance
“…Functional connectivity alterations in the temporal lobes between BD and MDD have been consistently reported by prior studies (He et al, ; Rive et al, ; Wang, Wang, Jia, Zhong, Niu et al, ; Wang, Wang, Jia, Zhong, Zhong et al, ). Interestingly, previous structural MRI studies have reported decreased cortical thickness in temporal as well as frontal areas including the ACC in individuals with BD (Hanford, Nazarov, Hall, & Sassi, ).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Functional connectivity alterations in the temporal lobes between BD and MDD have been consistently reported by prior studies (He et al, ; Rive et al, ; Wang, Wang, Jia, Zhong, Niu et al, ; Wang, Wang, Jia, Zhong, Zhong et al, ). Interestingly, previous structural MRI studies have reported decreased cortical thickness in temporal as well as frontal areas including the ACC in individuals with BD (Hanford, Nazarov, Hall, & Sassi, ).…”
Section: Discussionsupporting
confidence: 64%
“…For example, Sacchet et al () observed gray matter volume differences in the caudate nucleus for euthymic BD and both depressed and euthymic MDD participants compared to HC, and in the ventral diencephalon between the depressed MDD group and the other three groups. Rive et al () found different connectivity patterns in the default mode network (DMN) between groups of currently depressed MDD along with remitted MDD and BD individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found neural differences between depressed BP and MDD to be present during a variety of tasks requiring cognitive control function in the left posterior parietal lobe, left post central gyrus, medial frontal gyrus, anterior cingulate, left and right para‐hippocampal gyrus, left cerebellum, medial frontal gyrus, and the left post central gyrus, with MDD patients most commonly displaying hyperactivity compared to BP patients . The only group of studies comparing activation in remitted BP and MDD, done by Rive et al, found greater DLPFC activity in BP compared to MDD during emotion regulation but a lack of neural differences during visuospatial planning task . While previous studies have reported failed deactivation during cognition in each illness individually, only one other study has compared deactivation during a task involving a function of cognitive control in BP and MDD participants .…”
Section: Introductionmentioning
confidence: 99%
“…Advanced neuroimaging may yield clinically useful methods by which to differentiate major depressive episodes associated with BD from those associated with MDD (7,8). Resting state functional connectivity (rsFC) is one possible such method (9).…”
Section: Introductionmentioning
confidence: 99%